Islamic Financing Policy Scenario in the Agricultural Sector: Interpretative Structural Model Approach - Muhammad Yasir Yusuf; Hafiizh Maulana (Journal of Global Innovations in Agricultural Sciences)
Access to capital for farmers requires the intermediation function of Islamic financing amidst high business risks. The research aims to identify the appropriate construction of Islamic financing products in the agricultural sector to increase access to capital in the agricultural sector in Indonesia. The research method uses the Interpretative Structural Modeling (ISM) Analysis model. The study of Islamic agricultural financing was carried out with 3 structural elements namely purposes, constraints and policy recommendations. The findings of the research results establish 3 policy clusters. First, the construction of a parallel greeting contract model between Islamic Banking, Rice Mills, and Agents in the Warehouse Receipt System scheme. Second, strengthening farmers' access to Islamic financial institutions and adjusting Sharia financial contracts in farming capital at the central and regional levels. Third, Islamic Cooperative microfinance institutions and financial arrangements for Islamic financing in the agricultural sector. This research recommendation provides valuable insights and practical solutions for implementing Islamic financial products with an agribusiness system approach based on feasibility studies of financial arrangements and risk mitigation for agricultural financing.